Corporeality in Elderly People's Conception Who Partake in a Public Gym Program (Research, Society and Development, 2020)
This present study aimed at identifying the conception of elderly people, who partake in a public gym program in Rio de Janeiro, regarding the corporeality. In addition, the referred work is composed of a descriptive, exploratory study, with a qualitative approach, conducted with 18 elderly people, who attended a public academy program in the city of Rio de Janeiro. A form with guide questions and a semi-structured interview were used as the data collection instrument. The statements were recorded, transcribed in full and categorized thereafter. The data were discussed according to the Content Analysis. In the participants' statements, it was observed the association of the chronological age progression with the gain of experience and happiness, resulting from personal and social involvement among loved ones. The perception of the senile process is still manifested through concern in physical conservation, regarding the physiological features of aging (gray hair, wrinkles and sagging). Keeping psychological health contributes to vitality and healthy aging. These factors, once well worked on, have a positive impact on the process. Autonomy linked to the body through physical exercise did contribute to the satisfaction of the elderly, which contributes to health in the aging process. The participants point out to have chronic non-communicable diseases, such as arterial hypertension, whose maintenance is done through physical activity, in order to contribute, thus, to the increase in life expectancy. Accordingly, the elderly, in this study presented a dynamic perception regarding the corporeality associated with the aging process, as well as its benefits and mitigating factors.